2008
DOI: 10.1111/j.1439-0388.2008.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of the West Balkan Pramenka sheep types as revealed by microsatellite and mitochondrial DNA analysis

Abstract: Several different phenotypes of the native Pramenka sheep have been developed in the Balkan region for different environmental and socio-cultural conditions. Animals from seven West Balkan Pramenka sheep types were analysed for 15 microsatellite markers and for mitochondrial DNA (mtDNA) and the results were used to assess genetic variation within and among the types and to infer the genetic population structure of the Pramenka sheep. Mean expected heterozygosity and allelic richness over the microsatellite loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 32 publications
9
37
4
3
Order By: Relevance
“…Moderate genetic variation component estimated between the studied populations (5.29%) was similar to values reported for other Balkan sheep (Cínkulov et al, 2008), and somewhat higher than those reported for Greek breeds (Ligda et al, 2009). The low percentages of the variance explained by utility-wise (0.008, P < 0.01) and geography-wise (0.006, P < 0.05) grouping, compared with results reported in Indian sheep (Arora et al, 2011), suggest a low influence of specific selection strategies, but also a poor influence of the geographical isolation in the overall sampling area.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Moderate genetic variation component estimated between the studied populations (5.29%) was similar to values reported for other Balkan sheep (Cínkulov et al, 2008), and somewhat higher than those reported for Greek breeds (Ligda et al, 2009). The low percentages of the variance explained by utility-wise (0.008, P < 0.01) and geography-wise (0.006, P < 0.05) grouping, compared with results reported in Indian sheep (Arora et al, 2011), suggest a low influence of specific selection strategies, but also a poor influence of the geographical isolation in the overall sampling area.…”
Section: Discussionsupporting
confidence: 86%
“…Except for OarFCB128, these markers showed no correlation to the occurrence of null alleles and can be explained by a reduced effective size of the flocks in the studied populations. Although a comparison of the genetic diversity parameters described here with those reported in other populations is difficult because of different markers and sample sizes used, our results indicate values similar to those reported for the Balkan pramenka breeds (Cínkulov et al, 2008). In general, our analyses revealed higher within-breed variability than reported for selected breeds such as Sarda sheep, as expected for sheep populations that have not been highly pressured by selection (Arranz et al, 2001;Pariset et al, 2003).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations